"Seven Theses": Notes by a Brazilian Translator in the Twenty-first Century. (March 2018) - Lima, Roberto
Rodolfo Stavenhagen's classic "Seven Erroneous Theses about Latin America" seems not only to have endured but to have gained explanatory power in relation to a variety of topics in Brazil today: the relationship between the middle class (and the elite) and the Southeastern states in the last election, the government's options vis-à-vis major projects such as Belo Monte, the Workers' Party advocates' rhetoric in defense of the growth of the middle class, the disputes over the rights of indigenous peoples, and even the discourse of social movement leaders, co-opted by the Lula administration. Although the fourth thesis appears to have lost its strength, it still substantiates one of the key arguments in the text—that internal colonialism is critical for understanding Latin America. O clássico "Sete teses equivocadas sobre a América Latina, " de Rodolfo Stavenhagen, parece não somente ter resistido ao tempo, mas ter ganho capacidade explicativa em relação a uma variedade de tópicos no Brasil contemporâneo: o relacionamento entre a classe media (e a elite) e os estados do Sudeste na última eleição, as opções do governo vis-à-vis grandes projetos como Belo Monte, a retórica dos defensores do Partido dos Trabalhadores em defesa da ampliação da classe média, as disputas sobre os direitos dos povos indígenas, e até mesmo o discurso de líderes de movimentos sociais, estes últimos sob o controle do governo Lula. Mesmo que a quarta tese pareca ter perdido força, ela ainda corrobora um dos principais argumentos do texto: o colonialismo interno é fundamental para que se entenda a América Latina.